Non-governmental organisations and sustainable rural development in Lesotho - Vusi Mashinini; Gawie de Villiers (Acta Academica, 2002)
Non-governmental organisations are increasingly considered a viable source of development assistance for the promotion of sustainable development. This article analyses the contribution of non-governmental organisations to sustainable rural development, with special emphasis on agriculture, in Lesotho. The findings are that they have made a significant contribution, but that their efforts were not sustainable, due to the fact that the communities were not willing to forego their old lifestyles and accept the sacrifices needed to achieve the advances introduced by sustainable rural development. Communities need to embrace the challenges and changes aimed at improving their lifestyles.